Status of Children from Siri's Marriage (Case Study of Constitutional Court Decision No. 46/PUU-VIII/2010) - Nailah Ariqah; Rabbil Arya Pasyah; Ahmad Muzacky (CV. Rayyan Dwi Bharata, 2023)
This study aims to examine or analyze the Constitutional Court Decision Number 46/PUU-VIII/2010. This decision was made based on a request submitted by Aisyah Mokhtar to the Constitutional Court for a Judicial Review or re-examination of the Law which will be assessed whether the Law is contrary to the norms of the 1945 Constitution or not. Aisyah Mokhtar submitted this application to risk the civil relations rights of her son, Muhammad Iqbal Ramadhan, with his father, Moerdiono. This was done because Aisyah Mokhtar's marriage to Moerdiono was a marriage that was legalized according to religion but not according to the state (unregistered marriage) because marriage registration was not carried out. After this MK decision, children outside of marriage can have a civil relationship with their father and father's family. However, this envoy only applies to children out of wedlock from unregistered marriages (siri marriage) and not children out of wedlock as a result of adultery. Because if this decision is applied to children out of wedlock resulting from adultery, then the Constitutional Court delegates will be considered contrary to Islamic law. According to Islam, a child born from an adulterous relationship only has a relationship with his mother and his mother's family, and not with his father.